Challenges in seabird by‐catch mitigation. (27th November 2014) - Favero, M.; Seco Pon, J. P.
<x xml:space="preserve">Abstract</x> Read the Feature Paper: Significant reductions in mortality of threatened seabirds in a South African trawl fishery; other Commentaries on this paper: Minimizing seabird by‐catch in industrial fisheries and the Response from the authors: Problems and solutions for seabird bycatch in trawl fisheries